Analysis and Hygienic Assessment of the Educational Load of Secondary School Children in Tashkent (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Changes taking place in modern education, against the background of the deterioration of the state of health of students, make it necessary to analyze the educational schedule and assess its hygienic rationality. A significant number of disturbances in the analyzed schedules and study loads were identified, and the most typical mistakes in the structure of schedules were found.